Breech presentation management: A critical review of leading clinical practice guidelines. Issue 3 (May 2022) - Morris, Sara; Geraghty, Sadie; Sundin, Deborah
Abstract: Problem: Clinical practice guidelines are designed to guide clinicians and consumers of maternity services in clinical decision making, but recommendations are often consensus based and differ greatly between leading organisations. Background: Breech birth is a divisive clinical issue, however vaginal breech births continue to occur despite a globally high caesarean section rate for breech presenting fetuses. Inconsistencies are known to exist between clinical practice guidelines relating to the management of breech presentation. Aim: The aim of this review was to critically evaluate and compare leading obstetric clinical practice guidelines related to the management of breech presenting fetuses. Methods: Leading obstetric guidelines were purposively obtained for review. Analysis was conducted using the International Centre for Allied Health Evidence (iCAHE) Guideline Quality Checklist and reviewing the content of each guideline. Findings: Antenatal care recommendations and indications for Caesarean Section were relatively consistent between clinical guidelines. However, several inconsistencies were found among the other recommendations in terms of birth mode counselling, intrapartum management and the basis for recommendations. Discussion: Inconsistencies noted in the clinical practice guidelines have the potential to cause issues related to valid consent and create confusion among clinicians and maternity consumers. Conclusion: Clinical practice guidelines, which focus on the risks of a Vaginal Breech Birth without also discussing the risks of a Caesarean Section when a breech presentation is diagnosed, has the potential to sway clinician attitudes and impact birth mode decision-making in maternity consumers. To respect pregnant women's autonomy and fulfil the legal requirements of consent, clinicians should provide balanced counselling.